Preparation methods of composite materials, composite materials and electronic devices

By forming a multi-layer ceramic layer on the oxide layer of the titanium alloy material, the problems of low hardness and poor wear resistance of the oxide layer of the titanium alloy material are solved, and the wear resistance and gloss of the composite material are improved.

CN119753570APending Publication Date: 2025-04-04GOERTEK INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411754725.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The oxide layer of the existing titanium alloy materials has small hardness and poor wear resistance, which is easy to be damaged during use.

Method used

A multi-layer ceramic layer is formed on the oxide layer of the metal base material by using the sol-gel method, and an oxide sol is formed by reacting the metal alkoxide with the degluent agent, and the low-temperature sintering and high-temperature sintering are carried out to form a solid ceramic layer.

Benefits of technology

The wear resistance and structural strength of the composite material are improved, the protection effect of the oxide layer is enhanced, and the glossiness of the composite material is high and the appearance is good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753570A_ABST
    Figure CN119753570A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite material, a composite material and an electronic device. The preparation method comprises: providing a metal material substrate, the surface of the metal material substrate has an oxide layer; mixing a metal alkoxide with a disintegrator to form an oxide sol, wherein the concentration of the oxide sol is 0.5mol / L-1.0mol / L; coating multiple layers of the sol on the oxide layer, wherein after each layer of the sol is coated, the sol is dried, and the sol is subjected to low temperature sintering to form a solidified layer, wherein the temperature of the low temperature sintering is 150°C to 260°C; and high temperature sintering the multiple layers of the solidified layer to form a ceramic layer, wherein the temperature of the high temperature sintering is 400°C to 1000°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and more specifically, to a method for preparing a composite material, a composite material and an electronic device. Background Art

[0002] In the related art, electronic devices usually include metal housings. For example, the metal housing is made of titanium alloy material. The surface of the titanium alloy material can form an oxide layer of different colors on the surface by anodizing. However, the oxide layer has a low hardness and poor wear resistance, and is easily damaged during use.

[0003] Therefore, it is necessary to provide a new technical solution to solve the above technical problems. Summary of the invention

[0004] One object of the present invention is to provide a new technical solution for a method for preparing a composite material.

[0005] According to a first aspect of the present invention, a method for preparing a composite material is provided. The method comprises:

[0006] Providing a metal material substrate, wherein the surface of the metal material substrate has an oxide layer;

[0007] Mixing the metal alkoxide with a dissolving agent to form an oxide sol, wherein the concentration of the oxide sol is 0.5 mol / L-1.0 mol / L;

[0008] Coating multiple layers of the oxide sol on the oxide layer, wherein after each layer of the oxide sol is coated, the oxide sol is dried, and the oxide sol is subjected to low-temperature sintering to form a solidified layer, wherein the temperature of the low-temperature sintering is 150° C. to 260° C.;

[0009] The plurality of solidified layers are sintered at high temperature to form a ceramic layer, wherein the high temperature sintering temperature is 400°C to 1000°C.

[0010] Optionally, the metal alkoxide includes at least one of aluminum isopropoxide, silicon ethoxide, and zirconium isopropoxide.

[0011] Optionally, the disintegrator includes at least one of nitric acid, hydrochloric acid, sulfuric acid, and glacial acetic acid.

[0012] Optionally, the thickness of each solidified layer is 6 nm-15 nm.

[0013] Optionally, the thickness of the multi-layer solidified layer is 10nm-80nm.

[0014] Optionally, the refractive index of the ceramic layer is 1.4-1.6, the light transmittance of the ceramic layer is 89%-96%, and the color difference value ΔE of the ceramic layer is ≤2.

[0015] Optionally, during low-temperature sintering or high-temperature sintering, the heating rate is 0.5°C / min-2°C / min.

[0016] Optionally, during the drying, the drying temperature is 60° C.-100° C., the drying time is 5 min-10 min, the low-temperature sintering time is 20 min-30 min, and the high-temperature sintering time is 40 min-90 min.

[0017] According to a second aspect of the present invention, a composite material is provided. The composite material is prepared according to the method for preparing the composite material of the present invention.

[0018] Optionally, it comprises a metal material substrate and a ceramic layer, the surface of the metal material substrate has an oxide layer, and the ceramic layer covers the oxide layer.

[0019] Optionally, the material of the ceramic layer is at least one of SiO2, Al2O3, and ZrO2.

[0020] According to a third aspect of the present invention, an electronic device is provided, comprising the composite material of the present invention.

[0021] In the embodiment of the present invention, the metal alkoxide reacts with the dissolving agent to form an oxide sol, and the ceramic layer is formed on the surface of the oxide layer by the sol-gel method. The ceramic layer has high strength, can effectively protect the oxide layer, improves the wear resistance of the composite material, and the composite material has high gloss and good appearance.

[0022] In addition, the blank of the ceramic layer is not formed by coating once, but by coating a layer of oxide sol, drying the oxide sol to form a gel, and then sintering the gel at a low temperature to form a solidified layer. After forming a solidified layer, the next solidified layer is coated. In this way, the thickness of the blank formed by multiple solidified layers is uniform, which can effectively avoid the problem of uneven thickness of the solidified layer caused by excessive coating of oxide sol at one time.

[0023] In addition, low-temperature sintering can effectively improve the strength of the gel, avoiding uneven thickness of the blank due to the flow of the oxide sol when the oxide sol is coated next time. High-temperature sintering connects the powder particles inside each solidified layer and between layers, thereby improving the structural strength of the ceramic layer.

[0024] Further features and advantages of the present invention will become apparent from the following detailed description of exemplary embodiments of the present invention with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention.

[0026] Figure 1 is a flow chart of a method for preparing a composite material according to an embodiment of the present invention.

[0027] Figure 2 Schematic diagram of the structure of a composite material according to an embodiment of the present invention.

[0028] Description of reference numerals:

[0029] 10. Ceramic layer; 20. Oxide layer; 30. Metal material substrate. DETAILED DESCRIPTION

[0030] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present invention unless otherwise specifically stated.

[0031] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.

[0032] Technologies, methods, and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.

[0033] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0034] It should be noted that like reference numerals and letters refer to similar items in the following figures, and therefore, once an item is defined in one figure, it need not be further discussed in subsequent figures.

[0035] According to one embodiment of the present invention, a method for preparing a composite material is provided. Figure 1-Figure 2 As shown, the preparation method comprises:

[0036] Providing a metal material substrate, wherein the surface of the metal material substrate has an oxide layer;

[0037] Mixing the metal alkoxide with a dissolving agent to form an oxide sol, wherein the concentration of the oxide sol is 0.5 mol / L-1 mol / L;

[0038] Coating multiple layers of the oxide sol on the oxide layer, wherein after each layer of the oxide sol is coated, the oxide sol is dried, and the oxide sol is subjected to low-temperature sintering to form a solidified layer, wherein the temperature of the low-temperature sintering is 150° C. to 260° C.;

[0039] The plurality of solidified layers are sintered at high temperature to form a ceramic layer, wherein the high temperature sintering temperature is 400°C to 1000°C.

[0040] Specifically, the metal material substrate 30 can be a copper alloy substrate, an aluminum alloy substrate, a stainless steel substrate, a titanium alloy substrate, etc. Take the titanium alloy substrate as an example for illustration. The titanium alloy substrate is an alloy material prepared from titanium metal and other metals (for example, at least one of molybdenum, vanadium, chromium, manganese, iron, cobalt, nickel, copper, etc.). The surface of the metal material substrate 30 forms an oxide layer 20 through an oxidation process. The oxide layer 20 can reflect or interfere with the incident light, thereby presenting a color. Depending on the thickness of the oxide layer 20, the oxide layer 20 can present different colors, for example, yellow, purple, blue, light blue, silver, pink, cobalt blue, green, etc. Optionally, an anodizing process is used to form an oxide layer 20 on the surface of the metal material substrate 30. The thickness of the oxide layer 20 is controlled by controlling the current, time, voltage, etc. of the anodizing so that the oxide layer 20 presents different colors. Of course, the oxidation process is not limited to anodizing, and those skilled in the art can select according to actual needs.

[0041] Metal alkoxide is a metal organic compound containing MOC group generated by the reaction of metal and alcohol, wherein M is a metal ion and C is an organic group such as alkyl, alkenyl, etc. Metal alkoxide is a precursor for preparing oxide sol. Metal alkoxide can undergo hydrolysis and polycondensation reaction with a dissolving agent to form an oxide sol. Optionally, the metal alkoxide includes at least one of aluminum isopropoxide, silicon ethoxide, titanium isopropoxide, and zirconium isopropoxide. All of the above substances can react with a dissolving agent to generate an oxide sol. The quality of the oxide sol is uniform.

[0042] The main function of the disintegrator is to promote the solubilization process. The disintegrator is an electrolyte compound. When the disintegrator is dissolved in water, it can dissociate counterions with the opposite charge to the surface of the metal alkoxide. Optionally, the disintegrator includes at least one of nitric acid and sulfuric acid. All of the above substances can react with the metal alkoxide to form an oxide sol. The quality of the oxide sol is uniform.

[0043] In addition, the concentration of the oxide sol is 0.5mol / L-1mol / L. If the concentration of the oxide sol is too low, it is easy to cause the density of the solidified layer to be low; on the contrary, if the concentration is too high, aggregation precipitation is easy to occur in the oxide sol, resulting in low transmittance of the ceramic layer 10. When the concentration of the oxide sol is 0.5mol / L-1mol / L, it can ensure the high density of the solidified layer and avoid aggregation precipitation in the oxide sol. Optionally, the concentration of the oxide sol is 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1mol / L, etc.

[0044] After the oxide sol is formed, the oxide sol is coated on the oxide layer 20. In general, the amount of oxide sol coated each time is small, so multiple layers need to be coated to reach a set thickness. If the previously coated oxide sol is not solidified, it is easy to flow, especially in the next coating process, the previously coated oxide sol flows in a large range under the action of external force, so that the thickness of the oxide sol on the surface of the oxide layer 20 is uneven.

[0045] In this example, in order to ensure that the thickness of the oxide sol applied each time is uniform. After each application of the oxide sol, the oxide sol is solidified. During the solidification process, first, the oxide sol is dried to remove most of the water in the oxide sol. The drying temperature is 60°C-100°C. If the drying temperature is too low, the drying time is long and the efficiency is low; conversely, if the drying temperature is too high, large-aperture pores are easily formed in the solidified layer, causing the solidified layer to easily form defects during the sintering process. When the drying temperature is 60°C-100°C, the drying efficiency of the solidified layer is high and it is not easy for the solidified layer to form large-aperture pores during sintering. Optionally, the drying temperature is 60°C, 70°C, 80°C, 90°C, 100°C, etc. The oxide sol obtains a gel after drying.

[0046] Then, the gel is subjected to low temperature sintering at a temperature of 150°C to 260°C. After low temperature sintering, the gel forms a solidified layer. The thickness of the solidified layer is uniform. The oxide sol is further coated on the solidified layer, and then dried and sintered at low temperature to form another solidified layer. Adjacent solidified layers are connected together. When the total thickness of the multiple solidified layers reaches the set requirements, a blank is formed.

[0047] If the temperature of low-temperature sintering is too low, the strength of the formed solidified layer is low; if the temperature is too high, the solidified layer is prone to cracking. When the sintering temperature is 150°C to 260°C, the strength of the solidified layer is moderate and it is not easy to crack. Optionally, the temperature of low-temperature sintering is 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, etc.

[0048] Finally, the blank is subjected to high temperature sintering to form a ceramic layer 10. The temperature of the high temperature sintering is 400° C. to 1000° C. In this process, the blank is densified to form an integral structure. The ceramic layer 10 finally obtained has high hardness and good light transmittance.

[0049] If the temperature of high-temperature sintering is too low, the sintering time required is long, and the internal structure of the blank is easily not adjusted in place; if the temperature of high-temperature sintering is too high, thermal stress is easily formed in the blank, resulting in cracking of the blank. When the sintering temperature is 400°C to 1000°C, the sintering time is moderate, and the blank is not easy to crack. Optionally, the temperature of high-temperature sintering is 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, etc.

[0050] It should be noted that the time of the high temperature sintering and low temperature sintering is the holding time after the sintering temperature is greater than sintering temperature. Of course, the drying temperature, low temperature sintering temperature, high temperature sintering temperature and time are not limited to the above embodiments, and those skilled in the art can select according to actual needs.

[0051] In the embodiment of the present invention, the metal alkoxide reacts with the disintegrator to form an oxide sol, a gel is formed on the surface of the oxide layer 20 by a sol-gel method, the gel is sintered at a low temperature to form a solidified layer, and the solidified layer is sintered at a high temperature to form a ceramic layer 10. The ceramic layer 10 has high strength, can effectively protect the oxide layer 20 of the metal material substrate 30, improves the wear resistance of the composite material, and the composite material has high gloss and good appearance.

[0052] In addition, the blank of the ceramic layer 10 is not formed by coating once, but by coating a layer of oxide sol, drying the cap oxide sol to form a gel, and then sintering the gel at a low temperature to form a solidified layer. After forming a solidified layer, the next solidified layer is coated. In this way, the thickness of the blank formed by multiple solidified layers is uniform, which can effectively avoid the problem of uneven thickness of the solidified layer caused by excessive coating at one time.

[0053] In addition, low temperature sintering can effectively improve the strength of the gel, avoiding uneven thickness of the blank due to the flow of the oxide sol when the oxide sol is coated next time. High temperature sintering connects the powder particles inside each solidified layer and between layers, thereby improving the structural strength of the ceramic layer 10.

[0054] In one embodiment of the present invention, the thickness of each solidified layer is 6 nm-15 nm.

[0055] In this example, the oxide sol is evenly coated on the oxide layer 20 by dipping, pulling, spinning, spraying, etc. to form a thin layer. The thickness of the thin layer is controlled by controlling the amount of oxide sol discharged. The greater the thickness of the thin layer, the greater the thickness of the solidified layer; conversely, the smaller the thickness of the thin layer, the smaller the thickness of the solidified layer. If the thickness of the solidified layer is too large, the oxide sol is easy to flow during the coating process, resulting in uneven thickness; the smaller the thickness, the more times the coating is required, and the preparation efficiency is low. When the thickness of each solidified layer is 6nm-15nm, it can effectively ensure the uniform thickness of the solidified layer and make the preparation efficiency of the composite material high. Optionally, the thickness of each solidified layer is 6nm, 8nm, 10nm, 12nm, 14nm, 15nm, etc.

[0056] In one embodiment of the present invention, the thickness of the multi-layer solidified layer is 10nm-80nm.

[0057] As mentioned above, a multi-layer solidified layer is finally formed by coating each solidified layer with an oxide sol, drying for gelation, and low-temperature sintering. If the thickness of the multi-layer solidified layer is too small, the formed ceramic layer 10 is too thin, and the wear resistance is poor, the strength is low, and the oxide layer 20 cannot be effectively protected; if it is too thick, the blank is easy to crack during high-temperature sintering. When the thickness of the multi-layer solidified layer is 10nm-80nm, the ceramic layer 10 can have good wear resistance and high strength, and can avoid cracking of the blank during high-temperature sintering. Optionally, the thickness of the multi-layer solidified layer is 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, etc.

[0058] Of course, the thickness of each solidified layer and the thickness of multiple solidified layers are not limited to the above embodiments, and those skilled in the art can make selections according to actual needs.

[0059] In one embodiment of the present invention, the refractive index of the ceramic layer 10 is 1.4-1.6, the light transmittance of the ceramic layer 10 is 89%-96%, and the color difference value ΔE of the ceramic layer 10 is ≤2.

[0060] In this example, the refractive index, transmittance, color difference value, etc. of the ceramic layer 10 affect the appearance of the composite material. By controlling the material, thickness, etc. of the ceramic layer 10, the refractive index, transmittance and color difference value of the ceramic layer 10 can be controlled. A refractive index that is too small easily leads to a low glossiness of the ceramic layer 10; conversely, a refractive index that is too large easily leads to color deviation of the ceramic layer 10. When the refractive index of the ceramic layer 10 is 1.4-1.6, the glossiness of the ceramic layer 10 can be high and the color deviation of the ceramic layer 10 can be avoided.

[0061] If the light transmittance of the ceramic layer 10 is too low, the color and glossiness of the oxide layer 20 may be reduced; on the contrary, if the light transmittance of the ceramic layer 10 is too high, the thickness of the ceramic layer 10 needs to be thinned, which affects the strength of the ceramic layer 10. When the light transmittance of the ceramic layer 10 is 89%-96%, the color and glossiness of the oxide layer 20 can be ensured to be high, and the thickness of the ceramic layer 10 can be avoided to be small.

[0062] The color difference value △E represents the degree of difference between two colors. The larger the color difference value △E, the greater the difference between the two colors, and the smaller the color difference value △E, the smaller the difference between the two colors. If the color difference value of the ceramic layer 10 is too large, the color of the oxide layer 20 will deviate, resulting in a poor appearance of the composite material. When the color difference value △E of the ceramic layer 10 is ≤2, the color deviation of the oxide layer 20 can be effectively avoided, and the appearance of the composite material is good.

[0063] Optionally, the refractive index of the ceramic layer 10 is 1.4, 1.45, 1.5, 1.55, 1.6, etc. The light transmittance of the ceramic layer 10 is 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, etc. The color difference value ΔE of the ceramic layer 10 is 0.5, 1, 1.5, 2, etc.

[0064] Of course, the refractive index, transmittance, color difference value, etc. of the ceramic layer 10 are not limited to the above embodiments, and those skilled in the art can make selections according to actual needs.

[0065] In one embodiment of the present invention, during low temperature sintering or high temperature sintering, the heating rate is 0.5° C. / min-2° C. / min.

[0066] For example, when a heating furnace is used for low-temperature sintering or high-temperature sintering, the temperature needs to be gradually raised from room temperature to the sintering temperature during the sintering process. If the heating rate is lower than 0.5°C / min, the heating time is too long and the sintering efficiency is low; if the heating rate is higher than 2°C / min, the blank is prone to cracking and falling off. When the heating rate is 0.5°C / min-2°C / min, it can not only meet the higher sintering efficiency, but also effectively avoid the cracking and falling off of the blank. Optionally, the heating rate is 0.5°C / min, 0.8°C / min, 1.0°C / min, 1.2°C / min, 1.5°C / min, 1.8°C / min, 2°C / min, etc.

[0067] Of course, the heating rate is not limited to the above embodiments, and those skilled in the art can set it according to actual needs.

[0068] According to a second embodiment of the present invention, a composite material is provided, which is prepared according to the composite material preparation method of the present invention.

[0069] The composite material of the present invention at least includes all the beneficial effects of the above embodiments, which will not be described in detail here.

[0070] In one embodiment of the present invention, Figure 2 As shown, the composite material includes a metal material substrate 30 and a ceramic layer 10 . The surface of the metal material substrate 30 has an oxide layer 20 , and the ceramic layer 10 covers the oxide layer 20 .

[0071] The composite material has the characteristics of light weight, glossy surface, good appearance, good wear resistance and long service life.

[0072] In one embodiment of the present invention, the material of the ceramic layer 10 is at least one of SiO 2 , Al 2 O 3 , and ZrO 2 .

[0073] In this example, the ceramic layers 10 have relatively high hardness, good wear resistance, and high light transmittance.

[0074] Of course, the material of the ceramic layer 10 is not limited to the above embodiments, and those skilled in the art can set it according to actual needs.

[0075] According to a third embodiment of the present invention, an electronic device is provided, which includes the composite material of the present invention.

[0076] The electronic device may be a mobile phone, a smart watch, a computer, a VR device, an AR device, a speaker, etc. The composite material is used as a housing of the electronic device.

[0077] The electronic device of the present invention also includes at least all the beneficial effects of the above embodiments, which will not be elaborated here.

[0078] The following describes in detail the preparation method of the composite material of the present invention with specific examples and comparative examples. It is worth noting that the following description is only exemplary and not a specific limitation of the present invention.

[0079] Example 1

[0080] A method for preparing a composite material, the preparation method comprising: providing a titanium alloy substrate, the surface of the titanium alloy substrate having an oxide layer 20. Mixing a metal alkoxide with a dissolving agent to form a sol. The metal alkoxide is aluminum isopropoxide. In this step, first, aluminum isopropoxide is added to distilled water and stirred at 80°C for 1 hour. Then, the dissolving agent HNO3 is added and stirred continuously so that aluminum isopropoxide and HNO3 react fully. The reaction generates an alumina sol. In this example, the concentration of the alumina sol is 0.7 mol / L. Next, the alumina sol is coated on the surface of the oxide layer 20 by immersion pulling to form a thin layer. Each time a thin layer is coated, the thin layer is first dried at 80°C for 5 minutes, and then low-temperature sintered at 200°C for 20 minutes to obtain a solidified layer. A total of 2 coatings are performed to form a blank. The total thickness of the blank is 20 nm. Finally, the blank is subjected to high-temperature sintering at 400°C. The sintering time is 50 minutes. During the low-temperature sintering and high-temperature sintering processes, the heating rate is 1° C. / min. Finally, a ceramic layer 10 is formed on the oxide layer 20 .

[0081] Example 2

[0082] A preparation method of a composite material, the preparation method comprising: providing a titanium alloy substrate, the surface of the titanium alloy substrate having an oxide layer 20. Mixing a metal alkoxide with a dissolving agent to form a sol. Wherein, the metal alkoxide is aluminum isopropoxide. In this step, first, aluminum isopropoxide is added to distilled water and stirred at 80°C for 1 hour. Then, a dissolving agent HNO3 is added and stirred continuously so that aluminum isopropoxide and HNO3 react fully. The reaction generates an alumina sol. Wherein, the concentration of the alumina sol is 0.7 mol / L. Next, the alumina sol is coated on the surface of the oxide layer 20 by spraying to form a thin layer. For each coating of a thin layer, the thin layer is first dried at 80°C for 8 minutes, and then low-temperature sintered at 180°C for 25 minutes to obtain a solidified layer. A total of 4 coatings are performed to form a blank. The total thickness of the blank is 40nm. Finally, the blank is subjected to high-temperature sintering at 750°C. The sintering time is 60 minutes. During the low-temperature sintering and high-temperature sintering processes, the heating rate is 1° C. / min. Finally, a ceramic layer 10 is formed on the oxide layer 20 .

[0083] Comparative Example 1

[0084] A preparation method of a composite material, the preparation method comprising: providing a titanium alloy substrate, the surface of the titanium alloy substrate having an oxide layer. Mixing a metal alkoxide with a dissolving agent to form a sol. The metal alkoxide is aluminum isopropoxide. In this step, first, aluminum isopropoxide is added to distilled water and stirred at 80°C for 1 hour. Then, a dissolving agent HNO3 is added and stirred continuously so that aluminum isopropoxide and HNO3 react fully. The reaction generates an alumina sol. The concentration of the alumina sol is 1.2 mol / L. Next, the alumina sol is coated on the surface of the oxide layer by spraying to form a thin layer. For each coating of a thin layer, the thin layer is first dried at 80°C for 10 minutes, and then low-temperature sintered at 200°C for 25 minutes to obtain a solidified layer. A total of 4 coatings are performed to form a blank. The total thickness of the blank is 40 nm. Finally, the blank is subjected to high-temperature sintering at 750°C. The sintering time is 50 minutes. During the low temperature sintering and high temperature sintering process, the heating rate is 1°C / min. Finally, a ceramic layer is formed on the oxide layer.

[0085] Performance Test:

[0086] The refractive index, light transmittance, and color difference ΔE of the composite materials prepared by the preparation methods of Example 1, Example 2, and the comparative example were measured respectively, and the composite materials were subjected to a 4h vibration wear resistance test and the color effect of the composite materials was judged by observation. The final results are shown in Table 1.

[0087] Table 1 - Performance comparison of the composite materials of Example 1, Example 2 and Comparative Example

[0088] Refractive Index △E Light transmittance 4h vibration wear resistance Color effects Example 1 1.4 1.2 96% OK OK Example 2 1.6 1.5 91% OK OK Comparative Example 1.9 20 80% OK NG

[0089] As can be seen from Table 1, Example 1 is prepared by the preparation method of the present invention. Since the concentration of the oxide sol is controlled to be 0.7 mol / L in the preparation method, the low-temperature sintering temperature is 200°C, and the high-temperature sintering temperature is 400°C, the ceramic layer 10 with good performance is finally obtained. Example 2 is prepared by the preparation method of the present invention. Since the concentration of the oxide sol is controlled to be 0.7 mol / L in the preparation method, the low-temperature sintering temperature is 180°C, and the high-temperature sintering temperature is 750°C, the ceramic layer 10 with good performance is finally obtained. Among them, the refractive index of the ceramic layer 10 of Example 1 is 1.4, and the refractive index of the ceramic layer 10 of Example 2 is 1.6. The light transmittance of the ceramic layer 10 of Example 1 is 96%, and the light transmittance of the ceramic layer 10 of Example 2 is 91%. The color difference value △E of the ceramic layer 10 of Example 1 is 1.2, and the color difference rate of the ceramic layer 10 of Example 2 is 1.5. After 4 hours of vibration wear test, the appearance of the ceramic layer 10 of Example 1 and Example 2 is good and not damaged. The composite materials of Example 1 and Example 2 are brightly colored and shiny. However, in the preparation method of the comparative example, the concentration of the oxide sol is controlled to be 1.2 mol / L, and during the preparation process, aggregated precipitation is formed in the oxide sol. Finally, the ceramic layer 10 obtained after high-temperature sintering has a refractive index of 1.9, a light transmittance of 80%, and a color difference value ΔE of 20. After a 4-hour vibration wear test, relatively severe wear occurred, and the composite material had severe color deviation.

[0090] In summary, the preparation methods of Example 1 and Example 2 can effectively avoid the aggregation and precipitation of the oxide sol by controlling the concentration of the oxide sol to 0.5 mol / L-1 mol / L, avoid the contamination of the ceramic layer, and improve the transmittance of the ceramic layer 10. By controlling the temperature of low-temperature sintering to 150°C to 260°C and the temperature of high-temperature sintering to 400°C to 1000°C, the thickness of the solidified layer is uniform, and the thickness of the final blank is uniform. And the ceramic layer obtained after sintering has fewer defects, high strength, and high transmittance. The ceramic layer 10 prepared by this preparation method can effectively protect the oxide layer 20, improve the wear resistance of the composite material, and make the composite material have high gloss and good appearance.

[0091] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.

[0092] Although some specific embodiments of the present invention have been described in detail by way of example, it will be appreciated by those skilled in the art that the above examples are for illustration only and are not intended to limit the scope of the present invention. It will be appreciated by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present invention. The scope of the present invention is defined by the appended claims.

Claims

1. A method for preparing a composite material, characterized in that: include: Providing a metal material substrate, wherein the surface of the metal material substrate has an oxide layer; Mixing the metal alkoxide with a dissolving agent to form an oxide sol, wherein the concentration of the oxide sol is 0.5 mol / L-1.0 mol / L; Coating multiple layers of the oxide sol on the oxide layer, wherein after each layer of the oxide sol is coated, the oxide sol is dried, and the oxide sol is subjected to low-temperature sintering to form a solidified layer, wherein the temperature of the low-temperature sintering is 150° C. to 260° C.; The plurality of solidified layers are sintered at high temperature to form a ceramic layer, wherein the high temperature sintering temperature is 400°C to 1000°C.

2. The preparation method according to claim 1, characterized in that: The metal alkoxide includes at least one of aluminum isopropoxide, silicon ethoxide, and zirconium isopropoxide.

3. The preparation method according to claim 1, characterized in that: The debonding agent includes at least one of nitric acid, hydrochloric acid, sulfuric acid and glacial acetic acid.

4. The preparation method according to claim 1, characterized in that: The refractive index of the ceramic layer is 1.4-1.6, the light transmittance of the ceramic layer is 89%-96%, and the color difference value ΔE of the ceramic layer is ≤2.

5. The preparation method according to claim 1, characterized in that: When performing low-temperature sintering or high-temperature sintering, the heating rate is 0.5°C / min-2°C / min.

6. The preparation method according to claim 1, characterized in that: During drying, the drying temperature is 60°C-100°C, the drying time is 5min-10min, the low-temperature sintering time is 20min-30min, and the high-temperature sintering time is 40min-90min.

7. A composite material, characterized in that: The composite material is prepared according to the method for preparing a composite material according to any one of claims 1 to 6.

8. The composite material according to claim 7, characterized in that The invention comprises a metal material substrate and a ceramic layer. The surface of the metal material substrate has an oxide layer, and the ceramic layer covers the oxide layer.

9. The composite material according to claim 8, characterized in that The material of the ceramic layer is at least one of SiO2, Al2O3, and ZrO2.

10. An electronic device, characterized in that: Comprising the composite material according to any one of claims 7 to 9.